Biology and Ecology of Norway Spruce - Tjoelker, Mark G. (Springer, 2012)
Norway spruce (Picea abies L.) is an important tree species with a remarkable natural range throughout Europe and Asia, ranging from the Balkan Peninsula to Siberia in the north and from the French Alps in the west to the Sea of Okhotsk in the east. Wherever it occurs, it is a key component of both natural and managed forests. Norway spruce is the most economically valuable conifer in Europe, producing high-quality timber and wood products.